HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL DENGAN PENYESUAIAN DIRI PESERTA DIDIK DI SMP NEGERI 23 KERINCI - Indah Pitriani; Suryadi; Yasrial Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to This study aims to determine: 1) the interpersonalcommunication of students at SMP Negeri 23 Kerinci, 2) the self-adjustment ofstudents at SMP Negeri 23 Kerinci, and 3) to examine the relationship betweeninterpersonal communication and students' self-adjustment at SMP Negeri 23Kerinci. The background of this research is the still prevalent issue of correlationalproblems. The sample consisted of 113 students selected using a simple randomsampling technique. The research instrument used was a questionnaire. Theresults of the study show that: 1) the interpersonal communication of students at SMPNegeri 23 Kerinci falls into the inappropriate category, 2) the self-adjustment of studentsat SMP Negeri 23 Kerinci is categorized as fairly appropriate, and 3) there is a relationshipbetween interpersonal communication and self-adjustment of students at SMP Negeri 23Kerinci, with a correlation value of 0.075, indicating that a relationship exists betweenthese two variables.Keywords: interpersonal communication, self-adjustment, junior high schoolstudents